Morphological characteristic and criteria of invasiveness of pituitary adenomas. - Chernenko, О.; Ivanova, О.; Guk, N.; Danevych, Е.; Rudenko, S.; Sil’chenko, V.; Malysheva, Т. (Морфологія / Morphologia / Morfologìâ, 2016)
Backgound. Pituitary adenomas (PA) are benign tumors, originated from the anterior pituitary tissue in the most cases. The notion of "invasiveness" is important in the planning phase of their treatment and capability for the prediction of the results. Objective. Invasiveness of pituitary adenomas, which includes the peculiar nature of the spread and extent of destructive tumor growth beyond the arachnoid capsule, still can not demonstrate unambiguous correlation with other morphological criteria and morpho-functional characteristics of the tumor. Methods. In this article the experience of diagnostics and treatment of 41 patients with pituitary adenomas with clinical manifestations of invasive growth is considered. Among them 29 (71%) women and 12 (29%) men aged from 19 to 75 years old. Prerequisite for inclusion in the study group was the intraoperative confirmation of tumor invasion. Results. In the most cases tumors grew through the wall of the cavernous sinuses, suprasellar spread or grew in sphenoid sinus. Spread of the tumor in the hypothalamic region and infrasellyar into the nasal cavity and sinus of the sphenoid bone were observed rarely. Indirect signs of tumor "activity" – a nuclear polymorphism, sites "fetal" structure were identified in 42% of cases. Increased mitotic and proliferative activities of the tumor were observed in 41.5% of cases. Conclusion. Morphological criteria of pituitary adenoma invasiveness require further improvement.